2011
DOI: 10.17660/actahortic.2011.897.6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Est-Derived Molecular Markers, Trap and Vntrs, for Banana Research

Abstract: The advent of high-throughput sequencing technology has generated abundant information on DNA sequences for the genomes of many plant species. Expressed Sequence Tags (ESTs), which are unique DNA sequences derived from a cDNA library and therefore representing genes transcribed in specific tissues or at some stage of development, are one type of DNA sequences highly available today for many important crop species. Molecular markers are used for bridging DNA sequence information with particular phenotypes and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Most of the somaclonal variants clustered according to their phenotypic categories. Our results are in agreement with those of Garcia et al (2011).…”
Section: Cluster Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Most of the somaclonal variants clustered according to their phenotypic categories. Our results are in agreement with those of Garcia et al (2011).…”
Section: Cluster Analysissupporting
confidence: 93%
“…Krishna et al (2016) reported that plant tissue culture may generate genetic variability, that is, somaclonal variations as a result of gene mutation or changes in epigenetic marks. Garcia et al (2011) used TRAP markers to study genetic diversity in banana plants and they proved their efficiency in this regard. Same notes were reported by Abdellatif et al (2012) and Krishna et al (2015).…”
Section: Srap and Trap Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…New VNTR loci were discovered in the M. acuminata Calcutta 4 BAC end-sequence [41] from five fully sequenced consensi datasets, with validation for polymorphism conducted on genotypes contrasting in host plant resistance to Sigatoka disease [44]. Recently, [45] used a transcriptome database to design primers that were able to distinguish 32 VNTR and 119 target region amplified polymorphism (TRAP) alleles in 14 diploid Musa accessions.…”
Section: Variable Number Tandem Repeats (Vntr)mentioning
confidence: 99%